Growth stimulation of Bifidobacterium from human colon using daikenchuto in an in vitro model of human intestinal microbiota - Sasaki, Kengo (Sci Rep, 2021)
Daikenchuto (DKT) is a Japanese traditional herbal (Kampo) medicine containing ginseng, processed ginger, and Japanese or Chinese pepper. We aimed to determine how DKT affects human colonic microbiota. An in vitro microbiota model was established using fecal inocula collected from nine healthy volunteers, and each model was found to retain operational taxonomic units similar to the ones in the original human fecal samples. DKT was added to the in vitro microbiota model culture at a concentration of 0.5% by weight. Next-generation sequencing of bacterial 16S rRNA gene revealed a significant increase in the relative abundance of bacteria related to the Bifidobacterium genus in the model after incubation with DKT. In pure cultures, DKT significantly promoted the growth of Bifidobacterium adolescentis, but not that of Fusobacterium nucleatum or Escherichia coli. Additionally, in pure cultures, B. adolescentis transformed ginsenoside Rc to Rd, which was then probably utilized for its growth. Our study reveals the in vitro bifidogenic effect of DKT that likely contributes to its beneficial effects on the human colon.